The influence of smoothness and speed of stand-to-sit movement on joint kinematics, kinetics, and muscle activation patterns - Jeon, Woohyoung; Dong, Xuanliang Neil; Dalby, Ashley; Goh, Chung-Hyun (Frontiers in Human Neuroscience, 2024)
Background: Stand-to-sit (StandTS) is an important daily activity widely used in rehabilitation settings to improve strength, postural stability, and mobility. Modifications in movement smoothness and speed significantly influence on the kinematics, kinetics, and muscle activation patterns of this movement. Understanding the impact of StandTS speed and smoothness on movement control can provide valuable insights for designing effective and personalized rehabilitation training programs. Research question: To examine the impact of smoothness and speed in StandTS movements on joint kinematics, kinetics, muscle activation patterns, and postural stability during StandTS. Methods: Twelve healthy younger adults participated in this study. There were two StandTS conditions. In the reference condition, participants stood in an upright position with their feet shoulder-width apart on the force plate. Upon a visual cue, participants performed StandTS at their preferred speed. In the smooth condition, participants were instructed to perform StandTS as smoothly as possible, minimizing contact pressure on the seat. Lower leg kinetics, kinematics, and coordination patterns of muscle activation during StandTS were measured: 1) angular displacement of the trunk, knee and hip flexion; 2) knee and hip extensor eccentric work; 3) muscle synergy pattern derived from electromyography (EMG) activity of the leg muscles; and 4) postural sway in the anterior-posterior (A-P), medio-lateral (M-L), and vertical directions. Results: Compared to the reference condition, the smooth condition demonstrated greater eccentric knee extensor flexion and increased joint work in both the knee and hip joints. Analysis of specific muscle synergy from EMG activity revealed a significant increase in the relative contribution of hip joint muscles during the smooth condition. Additionally, a negative correlation was observed between knee extensor work and vertical postural sway, as well as hip extensor work and M-L postural sway. Conclusion: Smooth StandTS facilitates enhanced knee eccentric control and increased joint work at both the hip and knee joints, along with increased involvement of hip joint muscles to effectively manage falling momentum during StandTS. Furthermore, the increased contributions of knee and hip joint work reduced postural sway in the vertical and M-L directions, respectively. These findings provide valuable insights for the development of targeted StandTS rehabilitation training.